Compact continuum source finding for next generation radio surveys - Hancock, Paul; Murphy, T.; Gaensler, B.; Hopkins, A.; Curran, J. (Oxford University Press, 2012)
We present a detailed analysis of four of the most widely used radio source-finding packagesin radio astronomy, and a program being developed for the Australian Square Kilometer ArrayPathfinder telescope. The four packages: SEXTRACTOR, SFIND, IMSAD and SELAVY are shown to produce source catalogues with high completeness and reliability. In this paper we analyse the small fraction (~1 per cent) of cases in which these packages do not perform well.This small fraction of sources will be of concern for the next generation of radio surveyswhich will produce many thousands of sources on a daily basis, in particular for blind radiotransients surveys. From our analysis we identify the ways in which the underlying sourcefinding algorithms fail. We demonstrate a new source-finding algorithm AEGEAN, based on the application of a Laplacian kernel, which can avoid these problems and can produce complete and reliable source catalogues for the next generation of radio surveys.